AB0278 Investigation of poor prognostic factors among rheumatoid arthritis patients in turkbio registry. (12th June 2018) - Inanc, N.; Ertürk, Z.; Ozen, G.; Dalkılıç, E.; Koca, S.S.; Can, G.; Karatas, A.; Pehlivan, Y.; Yazici, A.; Cefle, A.; Akar, S.; Senel, S.; et al.
Abstract : Background: TURKBIO is the Turkish version of Danish DANBIO rheumatologic database which has been established in 2011. Patients' data including age, sex, disease type and duration, and previous or current treatment with conventional (cs), targeted synthetic (ts) and biological (b) DMARDs were collected. In 2016, the EULAR RA management guideline recommended assessment of certain prognostic factors while deciding the treatment strategy after the first csDMARD failure. Objectives: We examined the frequency and influence of these poor prognostic factors on treatment response in bDMARD and tsDMARD initiating RA patients enrolled in TURKBIO. Methods: 898 biological and targeted synteticDMARDs receiving RApatients from 8 participating centres ofTURKBIO werestudied. Seven investigated poorprognostic factors were: 1 Moderate to high disease activity(aftercsDMARD therapy), 2 Elevated acute phase reactants, 3 High swollen joint counts (≥4), 4 High RF/ACPA titers, 5 Combinations of the above, 6 Erosions, 7 Failure of ≥2 csDMARDs. The frequencies of these factors at treatment initiation and influence of these on achievement of remission/remission+low disease activity (LDA) according to DAS28-CRP at the 6th month of treatment were evaluated in overall any bDMARD and tsDMARD-receiving patients. Results: Among the prognostic factors; factors 1, 2, 4, 6 and 7 were found in over 60% of patients while factors 3 and 5 were present in about 30%. Factors 1 and 3 were more frequent in patients who were in moderate/high disease activity compared to those in remission +low disease activity (table 1). Same factors 1 and 3 were determined at higher percentage in non-remission than remission group (Factor 1: 93.4% vs. 82.2%, p<0.001; factor 3: 43% vs. 30.7%, p=0.002). These two factors were also significantly more frequent in patients withdrawn from the treatment (Factor 1: 93% vs. 85%, p<0.001; factor 3: 41% vs. 34%, p=0.038). In TNFi group besides factors 1 and 3, factors 5 and 7 were also significantly more frequent in non-remission group whereas, in the RTX group, only factor 1 was significantly more frequent in remission group. For the other bDMARDs and tsDMARD (ABA, TCZ, TOFA), we did not find any difference in poor prognostic factors among patients who did achieve remission and did not. Conclusions: Five of the seven poor prognostic factors were detected more than half of the RA patients at bDMARD and tsDMARD initiation in TURKBIO. Patients with poor prognostic factors especially factors 1 and 3 achieved remission less frequently. Additionally, there was a relationship between bDMARDs and tsDMARD withdrawal and factors 1 and 3. The influence of these factors was mainly observed in TNFi receiving group. Disclosure of Interest: None declared